PENGARUH PENGGUNAAN MULTIMEDIA POWER POINTT TERHADAP HASIL BELAJAR MAHASISWA PRODI PENDIDIKAN MATEMATIKA FKIP UMSU - Surya Wisada Dachi (MES: Journal of Mathematics Education and Science, 2018)
Abstract. The research objectives are: (1) To determine the effect of using multimedia power pointts on student learning processes, (2) Knowing the effect of using multimedia power pointts on student learning outcomes. This type of research is Classroom Action Research (CAR), which is to determine the effect of using multimedia power pointts on student learning outcomes of mathematics education study program FKIP UMSU. The results showed that the influence of multimedia power pointt on learning outcomes was very influential where the results of hypothesis testing obtained tcount of 6.71 while t table of 1.67 at the 5% level of significance (α = 0.05), it turns out tcount t table, then Ho is rejected Ha accepted.Keywords: Multimedia Power pointts and Student Learning Outcomes